Pengaruh Kredibilitas dan Karakteristik Opinion Leader terhadap Behavioral Intention Konsumen pada Media Sosial Instagram - Sri Hartini; Arbhie Nugraha Hanafi (Universitas Proklamasi 45 Yogyakarta, 2021)
This study aims to determine the effect of the information source’s credibility and characteristic towards opinion leadership, and the effect of opinion leadership on consumer behavioral intention in social media Instagram. The population in this study were all social media users who use Instagram as their fashion reference. The total sample used in this study was 168 people. The sampling method used in this research is purposive sampling. The result obtained from this study indicates that credibility and characteristic have a significant and positive effect on opinion leadership, and opinion leadership has a significant and positive effect on the intention to interact and intention to follow the advice.